GPX4 at the Crossroads of Lipid Homeostasis and Ferroptosis - Forcina, Giovanni C.; Dixon, Scott J. (Proteomics (Weinheim), 2019)
Oxygen is necessary for aerobic metabolism but can cause the harmful oxidation of lipids and other macromolecules. Oxidation of cholesterol and phospholipids containing polyunsaturated fatty acyl chains can lead to lipid peroxidation, membrane damage, and cell death. Lipid hydroperoxides are key intermediates in the process of lipid peroxidation. The lipid hydroperoxidase glutathione peroxidase 4 (GPX4) converts lipid hydroperoxides to lipid alcohols, and this process prevents the iron (Fe2+)‐dependent formation of toxic lipid reactive oxygen species (ROS). Inhibition of GPX4 function leads to lipid peroxidation and can result in the induction of ferroptosis, an iron‐dependent, non‐apoptotic form of cell death. This review describes the formation of reactive lipid species, the function of GPX4 in preventing oxidative lipid damage, and the link between GPX4 dysfunction, lipid oxidation, and the induction of ferroptosis.